Stabilizing techniques and guided imagery for traumatized male refugees in a German state registration and reception center: a qualitative study on a psychotherapeutic group intervention - Zehetmair, Catharina; Tegeler, Inga; Kaufmann, Claudia; Klippel, Anne; Reddemann, Luise; Junne, Florian; Herpertz, Sabine; Friederich, Hans-Christoph; Nikendei, Christoph (Journal of Clinical Medicine, 2019)
Refugees have an increased risk of developing mental health problems. Due to the unstable setting in refugee state registration and reception centers, recommended trauma-focused treatment approaches are often not applicable. For this purpose, we devised a suitable therapeutic approach to treat traumatized refugees in a German state registration and reception center: Group therapy, focusing on stabilizing techniques and guided imagery according to Reddemann (2017). From May 2017 to April 2018, we conducted semi-structured interviews with n = 30 traumatized refugees to assess their experiences with the stabilizing techniques and guided imagery in group sessions and self-practice. Participants mainly reported that they had more pleasant feelings, felt increasingly relaxed, and could better handle recurrent thoughts. Additionally, the participants noticed that their psychosocial functioning had improved. The main difficulties that participants encountered were feeling stressed, having difficulties staying focused, or concentrating on the techniques. During self-practice, the participants found it most challenging that they did not have any verbal guidance, were often distracted by the surroundings in the accommodation, and had recurrent thoughts about post-migratory stressors, such as insecurity concerning the future or the application for asylum. Our results show that stabilizing techniques and guided imagery according to Reddemann (2017) are a suitable approach to treat traumatized refugees living in volatile conditions.